Spike-landing motion of elite male volleyball players during official games - Quispe Marquez, W.; Masumura, M.; Ae, M. (International Journal of Sport & Health Science, 2011)
The purpose of this study was to investigate the motions during the airborne phase and their relations with single-legged landing position in elite male volleyball players during official games, and gain insights into techniques for safe landing. The spike-landing motions of four male world-level right-handed volleyball players were recorded with two high-speed video cameras during official games for a three-dimensional analysis. The results indicated a large trunk twist and a trunk left lean during the airborne phase of single-legged landings. The lower limbs reacted to the upper body motion differently for the left and right legs. The left hip extended during the last portion of the airborne phase to prepare for landing while the right hip continuously flexed and abducted, elevating the right leg, which resulted in left-legged landings. The results of one double-legged landing of a skilled player indicated that a compact trunk twist with a small left lean may have been why a straight body configuration was maintained and the right leg did not elevate as in the single-legged landings.